Recht und Religion in der europäischen Rechtstradition, Teil 2, Römisches Recht und Römische Kirche: ein rechtshistorischer Streifzug - Zimmermann, Reinhard (Zeitschrift der Savigny-Stiftung für Rechtsgeschichte. Kanonistische Abteilung, 2019)
Abstract Roman Law and Roman Church. A Foray in the Field of Legal History. This is the slightly amended text of a public lecture delivered at the invitation of the organizers of the 42nd German Legal History Conference in September 2018 in Trier. After briefly sketching the enormous range of the discipline of legal history, the lecture focuses on the law of contract and the law of succession; and it seeks to demonstrate the importance of Rome on the development of European private law: both the Rome of pagan antiquity and of the Christian Church